An assessment of the shore baitfishery in the Eastern Cape - Mackenzie, Bernard Louis (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2005)
The collection of bait organisms goes hand-in-hand with shore-angling in South Africa, hence the level of bait-collection can be used as an indicator of fishing effort and vice versa. This emphasises the importance of understanding the fisheries for bait organisms. In 1998 the South African fisheries policy was revised, culminating in the Marine Living Resources Act No. 18 (1998) which supported sustainable development, equitable access to resources and stability of the industry. The policy also dealt with the needs of subsistence fishers who had previously been all but ignored. This study looks to continue in this direction by investigating the opportunities for the establishment and management implications of small-scale commercial baitfisheries in the Eastern Cape. Data were collected from eight clearly demarcated sampling areas using the roving survey method. A total of 97 survey trips were undertaken between September 2001 and April 2003 and 469 interviews were conducted on individual anglers. The data was analysed and discussed on the basis of three wider study regions and this allowed for a more accurate and focussed assessment of the fishery area and the potential for its formalisation. Recreational fishers (91.5%) dominated in each of the three regions surveyed. The low number of subsistence fishers encountered in this study is not a standard pattern throughout South Africa. The dominance of local residents in the shore-fishery could have an important impact on the success of a formalised baitfishery in that the greater proportion of the potential market is accessible throughout the year. Most recreational shore-anglers were middle-aged (43.8 years ± 12.9 years), and hence at the peak of their earning years and this may contribute towards the potential success of a small-scale commercial baitfishery. Most anglers and baitfishers were of the opinion that all South Africans owned and were responsible for managing the living marine resources. The vast majority of recreational users paid for and were in possession of valid permits and approved of the baitfishery regulations. This implies that the greater majority of users recognise that the state is the rightful custodian of the resource and is responsible for management. No subsistence users were in possession of permits. Resource users in the Gamtoos to Tsitsikamma National Park region, where the inspection rate was highest, had the best knowledge of the regulations regarding both baitfishing (67.2% ± 38.8%) and angling (79.8 ± 21.4%). This substantiates the hypothesis that there is a direct correlation between knowledge of the regulations and the rate of inspection. About 475 000 angler-days/year were fished in the study area, with the highest number of angler-days recorded in or near urban and peri-urban areas. Bronze bream (65.9%) and dusky kob (61.1%) were the two most commonly targeted species, followed by white steenbras (31.7%), white musselcracker (31.4%) and blacktail (20.2%). A total of four purchased and 19 collected bait species was recorded during the study. Sardine, chokka and pink prawn were the most frequently encountered purchased bait. Red bait, sand prawn, mullet, siffie, sand mussel, bloodworm and saddleback were the most frequently encountered collected bait species. Sand prawn was identified as the preferred bait species for a wide range of angling species. The total quantity of bait organisms used per fishing trip was markedly less than the total amount collected per trip. The ban of off-road vehicles (ORV's) from beaches (20 January 2002) resulted in spatial shifts in angler effort in certain areas, suggesting that total effort has reduced in areas where ORV's were commonly used. Subsequent to the ban, fishers were encountered, on average, much closer to access points. The value of small-scale baitfisheries within the total study area was estimated at about R7 million per year. Across the entire study area red bait was identified as the most valuable bait in the rock-and-surf fishery in monetary terms, while sand prawn was also important. The findings led to the conclusion that small-scale commercial baitfisheries in the study area are potentially viable. Scenarios for the establishment of baitfisheries are suggested and discussed.
Keywords: Fishing baits -- South Africa -- Eastern Cape; Fishery management -- South Africa -- Eastern Cape; Fisheries -- South Africa -- Eastern Cape; Fishery -- Law and legislation -- South Africa